Rancang Bangun Aplikasi E-Learning di LBB Primagama Malang dengan Implementasi Konsep Gamifikasi - Khairy, Muhammad Shulhan; Wibowo, Dimas Wahyu; Syahrizal, Muhammad Dio (Department of Informatics Engineering, 2021)
Recently, e-learning as a learning media has been developed rapidly. But students have lack of interest to learn. We develop e-learning system with gamification concepts to solve that problem. Gamification concepts that implemented to the system includes point, badge, reward, and leaderboard. We also implement gamification element such as game mechanic, game design, and game thinking. The system tested to the students and got improvement 81,60% for interest to learn.